Grief & personal growth: reflection from Quran, hadith and modern medicine - Nasution Raduan, Nor Jannah; Md Rosli, Najwa Hanim; Razali, Zul Azlin; Sakhi Mohd, Muhammad Al Siddiq; Salleh, Mohd Razali (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2018)
Grief has been defined as the reaction towards loss with typical symptoms including sadness, anger, guilt, yearning, regret, loneliness, numbness and positive feelings related to individual’s personal experience. Grief has been postulated to occur when a safe and secure bond has been threatened. This loss can be an opportunity for personal growth. It is growth that emerges from difficult life events. It may occur during or after the process of grieving. We reviewed three cases related to grief and personal growth. Three cases were described where grief and personal growth were observed. Each case occurred in different situations. These different situations were; an adult child and caregiver of patient with dementia, a widow who loss her husband from drowning, and a cancer survivor who experienced psychological and spiritual growth from the loss and adverse life event. As a comparison three stories taken from the Quran and Hadith were analyzed to reflect on the three case discussions. The Quran and Hadith have mentioned stories of personal growth emerging from difficulties. The completeness of Islamic creed has never neglected the spiritual component in treating medical, physical and psychological illnesses. Islamic spirituality facilitates and enhances personal growth in the aftermath of any physical and psychological tribulations. It is important to merge the spiritual aspects of grief from Islamic perspective, as to aid those suffering from grief to attain personal and spiritual growth.